Pengaruh Persepsi Wajib Pajak atas Penerapan Pp No. 23 Th.2018, Pemahaman Perpajakan dan Sistem Administrasi Modernisasi Perpajakan terhadap Kepatuhan Wajib Pajak (Studi Kasus Sektor Umkm pada Kpp Pratama Jakarta Jatinegara Periode 2021) - Efrinal Efrinal; Putri Fitrilia Ariyanti (AKRUAL : Jurnal Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of Taxpayer’s Perceptions on the Implementation of Government Regulation Number 23 of 2018, Taxation Understanding and Tax Modernization Administration Systems on Taxpayer Compliance of Micro, Small, and Medium Business Enterprises Sector. The independent variables of this research are Taxpayer’s Perceptions on the Implementation of Government Regulation Number 23 of 2018, Taxation Understanding and Tax Modernization Administration Systems. The dependent variable of this research is the Compliance of Taxpayers of Micro, Small and Medium Business Enterprises Sector. Data collection techniques in this study were in the form of questionnaires (Survey on the taxpayer in Tax Office (KPP) Pratama Jakarta Jatinegara) and surrounding areas were obtained from 100 respondents listed as individual taxpayer or respondents via google form. This research method uses Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach and uses SmartPLS 3.0 software to analyze the data. The results of this study indicate that the Taxpayer's Perception of the Implementation of Government Regulation Number 23 of 2018 has a positive and significant effect on Taxpayer Compliance, Tax Understanding has a positive effect on Taxpayer Compliance and the Tax Modernization Administration System has a positive and significant impact on Taxpayer Compliance of Micro, Small and Medium Business Enterprises Sector.